Peningkatan Pertumbuhan Tanaman dengan Pemanfaatan Daun Gamal dan Duo Bio (Sekam Padi dan Bonggol Pisang) sebagai Media Tanam Berkelanjutan - Mutmainna, Mutmainna; MS, Andi Trisnowali; Asfar, Andi Muhammad Irfan Taufan; Nurannisa, Andi; Rasmiati, Rasmiati; Asfar, Andi Muhamad Iqbal Akbar; Eki Ikasari, Eki Ikasari (Unri Conference Series: Community Engagement, 2024)
Sustainable agriculture is the main focus in efforts to meet food needs and preserve the environment. Utilizing organic materials as an environmentally friendly alternative planting medium is one strategy that can be implemented. This service aims to evaluate the effectiveness of gamal leaves and duo bio (rice husks and banana stems) as sustainable planting media for plant growth. The implementation method for this community service is society participatory with three stages, namely the counseling stage, training stage and mentoring stage. The results of this service show that planting media containing gamal leaves and duo bio significantly increases plant growth compared to pure soil growing media. Planting media with a combination of gamal leaves and duo bio produced the highest plant growth, followed by planting media with gamal leaves, duo bio and pure soil. The use of gamal leaves and duo bio as an environmentally friendly alternative planting medium has proven to be effective in increasing plant growth. The use of this planting medium can be a sustainable solution to increase agricultural production and preserve the environment.